Robustness of the Process of Nucleoid Exclusion of Protein Aggregates in Escherichia coli - Neeli-Venkata, Ramakanth (2018)
Portuguese Foundation for Science and Technology provided funding to Jose Fonseca under grant number PTDC/BBB-MET/1084/2012. Academy of Finland vertical bar Biotieteiden ja Ympariston Tutkimuksen Toimikunta (Forskningsradet for Biovetenskap och Miljo) provided funding to Andre S. Ribeiro under grant number 257603.